1998
DOI: 10.2307/2640954
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Invasive Non-Indigenous Plants in Hurricane-Affected Subtropical Hardwood Forests

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 38 publications
(48 reference statements)
1
66
0
1
Order By: Relevance
“…In Jamaica, Bellingham et al (2005) found that hurricanes facilitated the spread of the exotic shrub Pittosporum undulatum Ventenat in native forests. Similar typhoon effects have been seen in Tahiti (Meyer 1994) and Florida (Horvitz et al 1998). However, other reviews have found that vegetation on some islands subject to frequent typhoons may regenerate rapidly following wind disturbances with little change in species composition (Brokaw & Walker 1991, Franklin et al 2004, Thompson et al 2007.…”
Section: Discussionmentioning
confidence: 53%
“…In Jamaica, Bellingham et al (2005) found that hurricanes facilitated the spread of the exotic shrub Pittosporum undulatum Ventenat in native forests. Similar typhoon effects have been seen in Tahiti (Meyer 1994) and Florida (Horvitz et al 1998). However, other reviews have found that vegetation on some islands subject to frequent typhoons may regenerate rapidly following wind disturbances with little change in species composition (Brokaw & Walker 1991, Franklin et al 2004, Thompson et al 2007.…”
Section: Discussionmentioning
confidence: 53%
“…lianas, Solanum spp., Dendrocnide spp., Calamus spp., Neolitsea dealbata) proliferate extensively in the understories of cyclone-disturbed rainforest fragments (Laurance 1991(Laurance , 1997. Such species are favoured by high light levels in the forest understorey following wind disturbance (Bellingham et al 1996;Horvitz et al 1998). Dense profusions of light-loving vines, such as Calamus spp., can dominate lowland forests in north Queensland that suffer recurring cyclone disturbance (Webb 1958).…”
Section: Species Invasionsmentioning
confidence: 99%
“…Invasive species not only directly impact human well being, but they also are recognized as agents that alter community structure and ecosystem function (for example, see ref. 4). In the United States alone, the damage wrought by invasive species totals approximately $122 billion per year (5).…”
mentioning
confidence: 99%